In Silico Development of Quorum‐Sensing Inhibitors. (7th June 2017) - Byeon, Jae‐Young; Sim, Jun; Ryu, Eun‐Ju; Sim, Jaehyun; Lee, Hwan; Cho, Kwang‐Hwi; Choi, Bong‐Kyu; Lee, Julian
Abstract : Quorum sensing (QS) is a chemical communication between bacteria, with which bacteria sense the population of their own species. Autoinducer‐2 (AI‐2) is a class of universal quorum‐sensing molecules, which is used by both Gram‐negative and Gram‐positive bacteria. The inhibition of AI‐2‐mediated QS has various practical applications, including the prevention of the formation of biofilm in dental gums. In this work, we develop a computational protocol for developing AI‐2 inhibitors. A challenging aspect of such an endeavor is that the receptor undergoes a large conformational change upon ligand binding. We combine several methods such as molecular docking with multiple conformations, molecular dynamics simulations, and molecular mechanics Poisson–Boltzmann computation, in order to estimate binding affinity of candidate molecules to a quorum‐sensing receptor. We apply our method to rank the substances in a chemical library. We indeed find a molecule that has a higher affinity than previously known ligands, thus showing the feasibility of the protocol for the development of quorum‐sensing inhibitors. Abstract :